PEMIKIRAN DANIEL GOLEMAN DALAM BINGKAI PEMBAHARUAN PENDIDIKAN ISLAM DI INDONESIA - Shoni Rahmatullah Amrozi (LP2M IAIN Jember (now UIN Kiai Haji Achmad Siddiq Jember), 2019)
In essence, the education process is the process of actualizing human potential. The process of developing the self-potential system has been offered perfectly in the Islamic teaching system, this is the reason why humans can carry out the tasks that have been charged by Allah. The actualization of human potential could be directed through the concept of developing